Role Playing in an Effort to Reduce Academic Procrastination for College Students - Reizki Maharani; Neviyarni S; Z. Mawardi Effendi (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2020)
Academic procrastination can be defined as a person's tendency to delay activities related to academics. We can find procrastination at every level of education, especially in college. One of the causes of procrastination in students because college students have greater responsibilities and demands than before. This research analyzed the effectiveness of role playing in information services to reduce student academic procrastination by uses a quantitative methods. The type of this research is Quasi Experiment with The Non Equivalent Control Group Design. The sample of this study were students majoring in Curriculum and Educational Technology, with 32 students in experimental group of and 32 students in control group. The research instrument used was a Likert Scale model, then it was analyzed using the Wilcoxon Signed Ranks Test and Rasch model. The results of this study generally indicate that information services using role playing are effective to reducing academic procrastination for students